O uso pedagógico do software Modellus na prática colaborativa de alunos para facilitar o desenvolvimento da aprendizagem significativa de cinemática - Silva, Ricardo Diniz Souza e (2014)
In recent decades the teaching and learning of physics in secondary schools have been widely discussed. In academia many proposed changes are described by experts. The use of computers as a teaching tool in education, favors the construction of physical knowledge, breaking stigmas where the teacher moves the position of the owner and developer of knowledge to mediator of learning. Observing the growing interest of young people by computers and the introduction of educational computing in schools, developed the thesis within the research line Digital Technologies in the Teaching of Science and Mathematics, in order to encourage educators and learners regarding the use of educational technologies Kinematics and learning. This research investigates facilitating the development of the learning process Cinematic using an educational approach that values learning articulating the operational and pedagogical use of the Software Modellus. So, we left for a pedagogical action, which was conceived and developed with the students of the 3rd year of high school, a state school in the city of Cascavel - Ce. To effect it was designed an educational approach , basing himself on some theoretical assumptions : David Ausubel (Theory of Meaningful Learning), Joseph Novak (Concept Maps), Armando Valente (The pedagogical use of computers, according to the constructivist approach) and Almeida (model learning development , constructed by the learner and aided by the interactive use of the computer ) . To proceed with the development of research, this researcher - educator adopted a qualitative research approach and characteristics of action research. To realize the pedagogical practice, we conducted 16 classes divided into two phases, totaling 32 class hours, the first being to diagnose prior knowledge using a traditional methodology with lectures, questionnaires, pre -and post - tests. The second phase aimed to develop a methodology for collaborative learning applied to the use of software to work Modellus the construction of charts, tables, and animations with students in the computer lab. We conclude that such a strategy favored constructivist learning and education process.